Mayer-Rokitansky-Küster-Hauser syndrome - Arga Kafi Perdana Kusuma; Bobby Indra Utama (Universitas Andalas, 2023)
Mayer–Rokitansky–Küster–Hauser syndrome (MRKH) is a syndrome characterized by uterine, cervix, and the two third of upper vagina aplasia which is the cause of incomplete development of the Müllerian duct. Reported a case of woman 28 years old, patient has not menstruated until now. The phenotype of the patient appears to be female, and with normal stature. Breast, axilla dan pubic hair distribution, fatty in buttocks and thigh developed normally. Fallopian tubes, uterine and 2/3 upper part of vagina were not formed. On gynecological clinical examination, found vaginal introitus with a vaginal sonde was 2 cm. On abdominal ultrasound examination, the uterus was seen as a line, right ovary measuring 2.93 x 2.59 cm and left ovary measuring 2.52 x 2.28 cm. The patient then underwent a diagnostic laparoscopic procedure, and found both right and left ovaries within normal limits, intact tubes, but no uterus was visible. Patient are planned for vaginoplasty.